Competencies on Execution of Village Government Authorities, Transparency, Public Participation and Accountability of Villages Fund Management - Shinta Ningtiyas Nazar; Rosita Wulandari; Syafrizal Syafrizal; Ayu Lestari (EAJ (Economic and Accounting Journal), 2021)
Authorities, transparency, and public participation to the accountability of village fund management and finds the obstacles to its implementation. This Research using multiple regression analysis, with convenience sampling and using questioners.  Results show competencies on the execution of village government authorities have effect negative and significant, contrary to Transparency have positive and significant, but Public Participation does not have effects. According to the result, competencies on the execution of village government authorities still low, villagers knows about village funds in Kecamatan Tigaraksa because they all get the benefit from village fund, and they only follow the instructions